Extreme Hot Weather Has Stronger Impacts on Avian Reproduction in Forests Than in Cities - Pipoly, Ivett; Preiszner, Bálint; Sándor, Krisztina; Sinkovics, Csenge; Seress, Gábor; Vincze, Ernő; Bókony, Veronika; Liker, András (Frontiers in Ecology and Evolution, 2022)
Climate change and urbanisation are among the most salient human-induced changes affecting Earth’s biota. Extreme weather events can have high biological impacts and are becoming more frequent recently. In cities, the urban heat island can amplify the intensity and frequency of hot weather events. However, the joint effects of heat events and urban microclimate on wildlife are unclear, as urban populations may either suffer more from increased heat stress or may adapt to tolerate warmer temperatures. Here, we test whether the effects of hot weather on reproductive success of great tits (Parus major) are exacerbated or dampened in urban environments compared to forest habitats. By studying 760 broods from two urban and two forest populations over 6 years, we show that 14–16 days-old nestlings have smaller body mass and tarsus length, and suffer increased mortality when they experience a higher number of hot days during the nestling period. The negative effects of hot weather on body mass and survival are significantly stronger in forests than in urban areas, where these effects are dampened or even reversed. These results suggest that urban nestlings are less vulnerable to extreme hot weather conditions than their non-urban conspecifics. This difference might be the result of adaptations that facilitate heat dissipation, including smaller body size, altered plumage and reduced brood size. Alternatively or additionally, parental provisioning and food availability may be less affected by heat in urban areas. Our findings suggest that adaptation to heat stress may help birds cope with the joint challenges of climate change and urbanisation.